Intelligent Paradigm in Grid Computing - Owoc, Mieczysław L. (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
Grid computing offers many advantages essential for business, especially using large scale distributed information. The goal of this paper is presentation of intelligent challenges that come from the grid computing technology. The paper consists of three sections: a short characteristics of general assumptions and features of GC starts the contents, then chosen models of grid computing are demonstrated and finally usability of intelligent methods is investigated. Concluding remarks end the paper.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 113-121